AGENT-BASED MODELING FOR TRAFFIC SIMULATION - BENHAMZA, KARIMA; ELLAGOUNE, SALAH; SERIDI, HAMID; AKDAG, HERMAN (Courrier du Savoir, 2014)
In  this  paper  we  develop  a  multi-agent  based  traffic  simulator  by  considering traffic  flows as emergent phenomena. The main  problem  of  agent-based  traffic  simulation  is how  to  reproduce  realistic  patterns  of  traffic  flow  at  both macroscopic and microscopic. The objective of simulation is a scenario of  traffic generated by the model  that should provide  the illusion of a real road scenario.